RECONSTRUCTION OF THE HIP JOINT IN CASE OF PATHOLOGICAL DISLOCATION OF THE HIP IN CHILDREN - Alpisbaev Ch.Sh; , Juraev A. M; Tapilov E. A; Kushabaev A. N (Scholar Express Journals, 2022)
According to Kh. Z. Gafarov et al. pathological dislocation of the hip occurs with the consequences of hematogenous osteomyelitis in 24.6% - 50% of cases [3]. Acute hematogenous osteomyelitis of the bones that form the hip joint occupies a special place and is difficult in terms of diagnosis, management of these patients and a large number of unsatisfactory treatment outcomes.
Keywords: osteomyelitis; hip joint; pathological dislocation of the hip; proximal end of the femur